Antibiotic-induced changes in the microbiota disrupt redox dynamics in the gut - Reese, Aspen T; Cho, Eugenia H; Klitzman, Bruce; Nichols, Scott P; Wisniewski, Natalie A; Villa, Max M; Durand, Heather K; Jiang, Sharon; Midani, Firas S; Nimmagadda, Sai N; O'Connell, Thomas M; Wright, Justin P; et al. (eLife, 2018)
How host and microbial factors combine to structure gut microbial communities remains incompletely understood. Redox potential is an important environmental feature affected by both host and microbial actions. We assessed how antibiotics, which can impact host and microbial function, change redox state and how this contributes to post-antibiotic succession. We showed gut redox potential increased within hours of an antibiotic dose in mice. Host and microbial functioning changed under treatment, but shifts in redox potentials could be attributed specifically to bacterial suppression in a host-free ex vivo human gut microbiota model. Redox dynamics were linked to blooms of the bacterial family Enterobacteriaceae. Ecological succession to pre-treatment composition was associated with recovery of gut redox, but also required dispersal from unaffected gut communities. As bacterial competition for electron acceptors can be a key ecological factor structuring gut communities, these results support the potential for manipulating gut microbiota through managing bacterial respiration.
Keywords: gut microbiota; redox potential; succession; antibiotics